THE LEGAL DIFFICULTIES GENERATED BY THE ALTERATION OF THE PROVISIONS REGARDING THE HEARING OF WITNESSES BY THE COURT WITHIN THE CIVIL PROCEDURAL CODE - Bogdan Sebastian GAVRILĂ; Oana Luiza Petruța POSMAC (Challenges of the Knowledge Society)
Since Law no. 310/2018 has altered the legal provisions of the Civil procedural code regarding the way in which witness testimony is to be obtained, a certain number of difficulties have been generated due to the fact that the actual hearing of witnesses has to occur in a radically different manner, thus imposing on the court some obligations which may prove troublesome in the future. The paper aims to establish some proper practices, in terms of ensuring for all parties a fair trial whilst also abiding by the new legal solutions.